ROAD USERS' PERCEPTIONS OF VISITORS' THERMAL COMFORT AND ITS RELATIONSHIP WITH THERMAL COMFORT ATTRIBUTES IN STREET CANYON, MH THAMRIN STREET, CENTRAL JAKARTA - Doksa Safira Tarigan; Jenny Indrastoeti Siti Poerwanti (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
MH Thamrin is a street canyon area experiencing global warming, and impact on the level of thermal comfort. This study aims to provide an overview of thermal comfort attributes and user perceptions of thermal comfort in Street Canyon, Jl. Based on the measurement results, it was found that the air temperature in the non-dense green space segment was higher than the dense green space segment, with a total average of 31.12°C and 30.27°C. Air humidity is more humid in the dense green space segment (62.69%) than the non-dense green space segment (62.16%). The amount of wind speed in the dense greenery segment is 1.41m/s, while for the non-dense greenery segment it is 0.99m/s. The lowest surface temperature in the non-dense greenery segment is around 26.95°C, and the highest is 39.1°C. The maximum surface temperature of the dense greenery segment is 33.9°C with a minimum surface temperature of 26.1°C. Through the results of road user perceptions, it was found that user perceptions in the dense green spaces segment fell into the moderate category (15.67≤X<19.33). Meanwhile, the level of thermal comfort in the segment of non-dense green spaces on MH Thamrin Street also in medium category. Spearman rank correlation analysis results show the entire thermal comfort attributes associated with user perceptions. Air temperature with user perception has a strong correlation and unidirectional relationship direction (correlation coefficient -0.853). Surface temperature and user perception is also strongly correlated with the direction of the relationship is not unidirectional (correlation coefficient -0.928). In contrast, air humidity and user perception also have a strong correlation, but the direction of the relationship is unidirectional (correlation coefficient 0.911). Wind speed and road user perceptions are strongly correlated and the direction of the relationship is unidirectional (correlation coefficient 0.893).